Investigation of antioxidant and antimicrobial activities of walnut (Juglans regia L.) kernel septum - Özşahin Delibaş, Elif Azize; Kıray, Esin (The European Research Journal, 2023)
Objectives: Walnut (Juglans regia L.) kernel septum (or septa) (WKS), a traditional nutraceutical material in China, has not been explored in detail. In this study, antimicrobial activity, total phenolic content (TPC) and antioxidant-oxidant status of WKS was investigated in case it may be clinically important in the management of various complications. Methods: The WKS was extracted with ethanol in a Soxhlet device. TPC of WKS was analysed by using Folin-Ciocalteu’s method. Antioxidant activity was obtained by using Rel Assay Diagnostics kits. The antimicrobial activity of WKS was evaluated against two Gram-positive (Staphylococcus aureus, Bacillus subtilis), one Gram-negative bacteria (Escherichia coli) and one fungus (Candida albicans) strains using the agar diffusion method. Results: The TPC of WKS was found to be 119.42 ± 2.39 mg GAE/gDW. It was determined that total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI) values were 7.542 ± 0.389 mmol/L, 3.718 ± 0.287 µmol/L and 0.049 ± 0.001, respectively. WKS selectively inhibited the growth of Gram-positive bacteria and fungus, while S. aureus was the most susceptible one with 16 mm of inhibition zone. Gram-negative bacteria was resistant to the extract. Conclusions: As far as we know, this paper is the first work that demonstrates the antioxidant-oxidant status of WKS by using the method described above, and moreover there are no scientific reports which have examined WKS in such a multidisciplinary experimental design. This study strongly supports the reported traditional use of WKS. Results indicated that WKS can be used as a pharmacological natural agent due to its high antioxidant and antimicrobial activities.